2017
DOI: 10.15567/mljekarstvo.2017.0202
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Fusarium mycotoxins in feedstuffs and cow milk sampled from Croatian farms during 2015

Abstract: Mycotoxins may contaminate food of animal origin due to the carry-over effect and represent a potential risk to human health. The problem of Fusarium mycotoxin contamination becomes an issue especially during rainy years characterised by substantial temperature changes. The aim of this study was to investigate into the level of Fusarium mycotoxins zearalenone (ZEN), deoxynivalenol (DON) and fumonisins (FUM) in maize silage (n=21), concentrated dairy cattle feeds (n=56) and cow milk samples (n=105), taken durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…NIV and DON were the most prevalent mycotoxins in our survey, followed by ENN B. DON is part of the multi-mycotoxin analysis in most surveys and has been found regularly in maize silages around the world [ 17 , 29 , 35 , 39 , 40 , 41 , 42 , 43 , 47 , 48 , 49 , 51 , 52 , 59 ]. In the global survey by Gruber-Dorninger et al (2019) [ 46 ], DON was the most prevalent mycotoxin in maize silages worldwide, with a 62% incidence.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…NIV and DON were the most prevalent mycotoxins in our survey, followed by ENN B. DON is part of the multi-mycotoxin analysis in most surveys and has been found regularly in maize silages around the world [ 17 , 29 , 35 , 39 , 40 , 41 , 42 , 43 , 47 , 48 , 49 , 51 , 52 , 59 ]. In the global survey by Gruber-Dorninger et al (2019) [ 46 ], DON was the most prevalent mycotoxin in maize silages worldwide, with a 62% incidence.…”
Section: Discussionmentioning
confidence: 90%
“…Over the course of three years, 8.3% of the silage samples exceeded the EU regulation for DON and 12.0% for ZEN. In previous literature, concentrations regularly exceeded the EU regulations for DON or ZEN in maize silages [ 29 , 39 , 40 , 41 , 42 , 45 , 46 , 48 , 49 , 52 , 59 ]. Pleadin et al (2017) [ 59 ] found that 4.8% of maize silages in 2015 in Croatia exceeded the EU regulation for ZEN, and 9.5% for DON.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The danger of the presence of mycotoxins in feed for cattle and other farm animals, in addition to the harm posed to livestock health and reduced productivity [30,31], is complemented by the risk of their transfer to animal products—mainly milk [32,33,34,35], eggs and meat [36,37,38,39]—and thus their inclusion in the human food chains [40,41,42]. First of all, this refers to non-polar toxins, capable of bioaccumulation [43].…”
Section: Introductionmentioning
confidence: 99%